Third-Person Self-Knowledge, Self-Interpretation, and Narrative (Contributions to Phenomenology, In Cooperation with The Center for Advanced Research in Phenomenology,, 2018)
This volume answers questions that lead to a clearer picture of third-person self- knowledge, the self-interpretation it embeds, and its narrative structure. Bringing together current research on third-person self-knowledge and self-interpretation, the book focuses on third-person self-knowledge, and the role that narrative and interpretation play in acquiring it. It regards the third-personal epistemic approach to oneself as a problem worthy of investigation in its own right, and makes clear the relation between third-person self-knowledge, self-interpretation, and narrative capacities. In recent years, the idea that each person is in a privileged position to acquire knowledge about her own mental states has come under attack. A growing body of empirical research has cast doubt upon the existence of what philosophers call 'first person self-knowledge', i.e., knowledge about our mental states that is often thought to be immediate, transparent, and authoritative. This line of thought has led some philosophers to claim that what seems to be 'first-person self-knowledge' is really just 'third-person self-knowledge,' i.e., knowledge about our mental states that is inferential, opaque, and fallible. This book discusses challenges for first-person knowledge and explores the true nature of third-person knowledge.